Electrically induced torque decrease reflects more than muscle fatigue. Issue 4 (30th August 2014) - Papaiordanidou, Maria; Stevenot, Jean‐Damien; Mustacchi, Valerie; Vanoncini, Michele; Martin, Alain
ABSTRACT The aim of the study was to compare the fatigue induced by different electrical stimulation (ES) protocols. The triceps surae muscle of 8 healthy subjects was fatigued with 4 protocols (30 Hz−500 μs, 30 Hz−1 ms, 100 Hz−1 ms, and 100 Hz−500 μs), composed of 60 trains (4 s on–6 s off), delivered at an intensity evoking 30% of maximal voluntary contraction (MVC). Fatigue was quantified by ES and MVC torque decreases. The amplitude of the twitch delivered at the intensity and pulse width used in each fatiguing protocol (twitch at Istim) was analyzed. All parameters decreased significantly after all protocols. The ES torque decrease correlated positively with the twitch decrease elicited at Istim only for the 30‐Hz protocols. Results show that, during the 100‐Hz protocols, phenomena not related to the fatigue of the solicited motor units may occur, including changes in the excitability threshold of the axonal terminal branches. Muscle Nerve 50: 604–606, 2014